2013
DOI: 10.3390/ijerph10104690
|View full text |Cite
|
Sign up to set email alerts
|

Was Mandatory Quarantine Necessary in China for Controlling the 2009 H1N1 Pandemic?

Abstract: The Chinese government enforced mandatory quarantine for 60 days (from 10 May to 8 July 2009) as a preventative strategy to control the spread of the 2009 H1N1 pandemic. Such a prevention strategy was stricter than other non-pharmaceutical interventions that were carried out in many other countries. We evaluated the effectiveness of the mandatory quarantine and provide suggestions for interventions against possible future influenza pandemics. We selected one city, Beijing, as the analysis target. We reviewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Of the included studies, 17 were cost-effectiveness analyses [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Cost-utility analyses were performed in 13 studies [43][44][45][46][47][48][49][50][51][52][53][54][55], and four studies performed cost-benefit analyses [56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included studies, 17 were cost-effectiveness analyses [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Cost-utility analyses were performed in 13 studies [43][44][45][46][47][48][49][50][51][52][53][54][55], and four studies performed cost-benefit analyses [56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study included future non-related healthcare costs [51]. With respect to costs outside the healthcare sector, 24 studies included productivity losses due to short-term absenteeism, transportation (two studies) [39,45], administration (one study) [41], treatment (one study) [39], presenteeism (one study) [49],and energy savings (one study) [45].…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed 1 intervention study (18), 5 observational studies (6,(19)(20)(21)(22), and 10 simulation studies (Appendix Tables 9, 10). Miyaki et al (18) conducted an intervention study in Japan during 2009-2010 involving 2 companies.…”
Section: Quarantine Of Exposed Personsmentioning
confidence: 99%
“…Among the observational studies, Li et al (20) estimated that the mandatory quarantine policy in Beijing during the influenza A(H1N1)pdm09 pandemic reduced the number of cases at the peak of the epidemic by a factor of 5 compared with a projected scenario without the intervention, and also delayed the epidemic peak, albeit at high economic and social costs (20). Similar to the intervention study in Japan, van Gemert et al (21) reported an increased risk for infection among household contacts who were concurrently quarantined with an isolated person and estimated that the risk for infection increased with a longer duration of quarantine.…”
Section: Quarantine Of Exposed Personsmentioning
confidence: 99%
“…We identified nine cost studies [11,14,15,17,[23][24][25][26][27], and four simulation studies relating to contact tracing and contact quarantine in outbreak scenarios [22,[36][37][38]. Tables 3 and 4 summarise the cost information from these studies (the original extracted data in original currencies and units can be found in the supplementary spreadsheet).…”
Section: Tracing and Quarantine Of Contactsmentioning
confidence: 99%